Development of Assessment Media Using Wondershare Quiz Creator for Evaluation Effectiveness for Teachers in Dompu Regency - Nasruddin Nasruddin; Muhammad Wahyu Setiyadi (STKIP Taman Siswa Bima, 2023)
The increasingly rapid development of technology has spurred the world of education to adapt to the progress of the digital world. Minister of National Education Regulation number 16 of 2007 mandates that one of the core competencies of teachers is to carry out assessments and evaluations of learning outcomes. Technology integration is one of the main characteristics of education today. The use of computers, the internet, smart devices and educational applications is becoming increasingly common in educational settings. Teachers must be able to integrate media into their daily teaching process. The problems that occur at SDN 32 Woja can be overcome by computerization in making questions. Research and Development (RnD) is the type of research used in this research. RnD is a highly effective research strategy or method for improving practice. The validation results of the computer mathematics learning assessment tool created by quiz maker Wondershare achieved an average percentage of subject matter experts of 90.25%. Based on the results of limited experiments, the average student response rate in the very interesting category was 80.21%. In summary, it can be concluded that based on students' answers, the effectiveness of the mathematics learning assessment tool using Wondershare quiz creation software is considered very effective, with an average assessment percentage of 83.26%, which means this learning assessment tool is suitable for use.